Persepsi citra tubuh dan kendala untuk menurunkan berat badan pada remaja SLTP di Kota Yogyakarta dan Kabupaten Bantul - Noviani Tarigan; Hamam Hadi; Madarina Julia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2005)
Background: The prevalence of obesity in children and adolescents is increasing, both in the developed and developing countries. Obesity has been reported to be related to the impairment of body image, but this association has not been studied among Indonesian adolescents.Objective: To assess the perception of body image and the obstacles for reducing body weight in obese junior high school adolescents in the District of Yogyakarta and Bantul.Methods: This is a cross sectional study, using both quantitative and qualitative approaches. Body images were assessed using Body Image Assessment for Obesity (BIA-O) with 8 figures. In depth interview were used to assess the perceptions of body images and the obstacles in reducing body weight faced by the obese adolescents.Results: Obese adolescents had significantly larger dissatisfaction to their body images compared to their non-obese peers, i.e. mean (95%CI) scores of dissatisfaction of 1.89 (1.69 – 2.08) in obese adolescents compared to –0.27 (-0.49 to 0.05) in non-obese adolescents. Most of the obese adolescents had tried to reduce their weight, mostly in order to have a better looks, but failures and hardships in the efforts had made most of them stopped trying.Conclusion: Obese adolescent were not satisfied with their image. Most of them had tried to reduce body weight but failures had made them stop trying.